Product Innovation Through Chip Making Training Bidara Leaves to Improve The Community's Economy Buhudaa Village, Gorontalo Province - Mardin, Herinda; Taan, Hapsawati (Panrannuangku Jurnal Pengabdian Masyarakat, 2024)
Innovation products are able to help the economy and provide knowledge to the community or village residents. Especially how to package a product to make it more attractive. With KKN, students are expected to be able to become an active, creative and innovative part of society, involved in the dynamics that occur in society. The activities carried out were Leaf Bidara UMKM Product Innovation and Product Packaging for the Community in Buhudaa Village, Batudaa Beach District, Gorontalo Regency. The methods in this activity are training and demonstration. The form of training is by providing material related to how to make bidara leaf chips and participants are trained to make bidara leaf chips. There were 15 participants who took part in this activity who were housewives and young people from Karang Taruna Buhudaa village. The activity was carried out on September 9 2024 at the Buhudaa village office hall, Batudaa Pantai District, Gorontalo Regency. The stages of this activity are the preparation stage, implementation stage, organoleptic test stage and evaluation stage. The training activity for making bidara leaf chips in Buhudaa village went smoothly and the activity participants were very enthusiastic during the activity process. Based on the results of organoleptic tests on the results of bidara leaf chips in training regarding aroma, taste, color and texture, they were very well received by the panelists.